Increased Frequency of Diabetic Ketoacidosis: The Link With COVID-19 Pandemic - d’Annunzio, Giuseppe; Bassi, Marta; De Rose, Elena Lucia; Lezzi, Marilea; Minuto, Nicola; Calevo, Maria Grazia; Gaiero, Alberto; Fichera, Graziella; Borea, Riccardo; Maghnie, Mohamad (Frontiers in Clinical Diabetes and Healthcare, 2022)
Aims: Diabetic ketoacidosis represents the most severe metabolic derangement due to prolonged lack of insulin, and can be observed either at type 1 diabetes diagnosis or thereafter. Diabetic ketoacidosis, sometimes due to delayed recognitionis a life-threatening condition. Prompt diagnosis is mandatory to prevent its consequences, mainly neurological. COVID-19 pandemic and the lockdown reduced the availability of medical care and the access to hospital. The aim of our retrospective study was to compare the frequency of ketoacidosis at type 1 diabetes diagnosis among the lockdown-post lockdown period and the two previous calendar years, in order to evaluate the effect of COVID-19 pandemic. Patients and Methods: We retrospectively evaluated clinical and metabolic data at pediatric type 1 diabetes diagnosis in Liguria Region during 3 different time periods: calendar year 2018 (Period 1), calendar year 2019 up to February 23rd,2020 (Period 2) and since February 24th, 2020 up to March 31th 2021 (Period 3). Results: We analyzed 99 newly-diagnosed T1DM patients since 01/01/2018 to 31/03/2021. Briefly, a younger age at disease diagnosis was observed in Period 2 patients as compared to Period 1 patients (p=0.03). Frequency of DKA at T1DM clinical onset was similar in Period 1 patients (32.3%) and Period 2 patients (37.5%), while significantly increased in Period 3 patients (61.1%) as compared to Period 2 patients (37.5%) (p=0.03). pH values were similar in Period 1 patients (7.29+0.14) and in Period 2 patients (7.27+0.17), while were significantly lower in Period 3 patients (7.21+0.17) as compared to Period 2 patients (p=0.04). Conclusions: We observed an increased frequency of diabetic ketoacidosis in newly diagnosed pediatric patients in Liguria Region during and after the lockdown period as compared to previous calendar years. Delayed diagnosis subsequent to restrictions imposed by the lockdown and reduced access to health care structures might be responsible. Increased awareness of ketoacidosis by means of social and medical sensitizing campaigns is mandatory.